Treatment-seeking behavior for malaria among communities in Indonesia: A systematic review - Philothra, Biodya D.; Alona, Ivana; Situmorang, Elizabeth; Limbardon, Patrick; Salsalina, Viktris G. (Narra J, 2023)
Indonesia stands as one of the nine malaria-endemic countries in Southeast Asia with a total of 443,530 cases in 2022. Eastern Indonesia is listed as an area with high malaria endemicity and the Indonesian government has set a target of eliminating malaria by 2030. From 2010 to 2014, the number of malaria cases decreased but stagnated until 2020 and have continued to increase. Stagnation may occur as a result of many non-medical treatment-seeking behaviors. The aim of this systematic review was to provide a summary and overview of malaria treatment-seeking behavior among communities in several regions in Indonesia. The searches were conducted through four databases (Cochrane, PubMed, Google Scholar, and ScienceDirect) using medical subject headings (MeSH) "treatment-seeking behavior" OR "health-seeking behavior" AND "malaria" AND "Indonesia". This systematic review was limited to studies conducted in Indonesia that were published between 2013 and 2023 using either a quantitative or qualitative approach. Out of 2831 studies, a total of thirteen studies were included. The pattern of seeking malaria treatment varied between doing nothing or no action, self-treatment (purchasing drugs at pharmacies and consuming leftover medicines), traditional medicine, and medical treatment (public health facilities or malaria control clinics). Those behaviors are attributed to education level, socioeconomic level, occupation, distance from home to health facilities, geographical conditions, and people's perceptions of malaria and antimalarial medicines. There is still a range of malaria treatment-seeking behavior outside of recommended medical treatment in communities in several regions in Indonesia. The phenomenon of medical pluralism and syncretism requires approaches from various sectors in order to achieve a malaria-free Indonesia by 2030.